Efficacy of Ciprofloxacin/Celecoxib combination in zebrafish models of amyotrophic lateral sclerosis. Issue 10 (11th September 2020) - Goldshtein, Hagit; Muhire, Alexandre; Petel Légaré, Virginie; Pushett, Avital; Rotkopf, Ron; Shefner, Jeremy M.; Peterson, Randall T; Armstrong, Gary A. B.; Russek‐ Blum, Niva
Abstract: Objective: To evaluate the efficacy of a fixed‐dose combination of two approved drugs, Ciprofloxacin and Celecoxib, as a potential therapeutic treatment for amyotrophic lateral sclerosis (ALS). Methods: Toxicity and efficacy of Ciprofloxacin and Celecoxib were tested, each alone and in distinct ratio combinations in SOD1 G93R transgenic zebrafish model for ALS. Quantification of swimming measures following stimuli, measurements of axonal projections from the spinal cord, neuromuscular junction structure and morphometric analysis of microglia cells were performed in the combination‐ treated vs nontreated mutant larvae. Additionally, quantifications of touch‐evoked locomotor escape response were conducted in treated vs nontreated zebrafish expressing the TARDBP G348C ALS variant. Results: When administered individually, Ciprofloxacin had a mild effect and Celecoxib had no therapeutic effect. However, combined Ciprofloxacin and Celecoxib (Cipro/Celecox) treatment caused a significant increase of 84% in the distance the SOD1 G93R transgenic larvae swam. Additionally, Cipro/Celecox elicited recovery of impaired motor neurons morphology and abnormal neuromuscular junction structure and preserved the ramified morphology of microglia cells in the SOD1 mutants. Furthermore, larvae expressing the TDP‐43 mutation displayed evoked touch responses that were significantly longer in swim distance (110% increase) and significantly higher in maximal swim velocity ( 44% increase) when treated with Cipro/Celecox combination. Interpretation: Cipro/Celecox combination improved locomotor and cellular deficits of ALS zebrafish models. These results identify this novel combination as effective, and may prove promising for the treatment of ALS.